Influence of collagen and chondroitin sulfate (CS) coatings on poly-(lactide-co-glycolide) (PLGA) on MG 63 osteoblast-like cells - Vandrovcová, M; Douglas, T; Hauk, D; Grössner-Schreiber, B; Wiltfang, J; Bačáková, L; Warnke, P H (Physiological research, 2011)
Poly-(lactide-co-glycolide) (PLGA) is an FDA-approved biodegradable polymer which has been widely used as a scaffold for tissue engineering applications. Collagen has been used as a coating material for bone contact materials, but relatively little interest has focused on biomimetic coating of PLGA with extracellular matrix components such as collagen and the glycosaminoglycan chondroitin sulfate (CS). In this study, PLGA films were coated with collagen type I or collagen I with CS (collagen I/CS) to investigate the effect of CS on the behaviour of the osteoblastic cell line MG 63. Collagen I/CS coatings promoted a significant increase in cell number after 3 days (in comparison to PLGA) and after 7 days (in comparison to PLGA and collagen-coated PLGA). No influence of collagen I or collagen I/CS coatings on the spreading area after 1 day of culture was observed. However, the cells on collagen I/CS formed numerous filopodia and displayed well developed vinculin-containing focal adhesion plaques. Moreover, these cells contained a significantly higher concentration of osteocalcin, measured per mg of protein, than the cells on the pure collagen coating. Thus, it can be concluded that collagen I/CS coatings promote MG 63 cell proliferation, improve cell adhesion and enhance osteogenic cell differentiation.
Keywords: Collagen Type I; Lactic Acid; viabilita buněk; Cell Line; testování materiálů; Cell Proliferation; osteogeneze; Polylactic Acid-Polyglycolic Acid Copolymer; osteoblasty; Materials Testing; kolagen typu I; Osteoblasts; Cell Survival; Chondroitin Sulfates; kultivované buňky; biokompatibilní potahované materiály; kyselina mléčná; Coated Materials, Biocompatible; lidé; Humans; kopolymer kyseliny glykolové a mléčné; Tissue Scaffolds; buněčné linie; proliferace buněk; Cells, Cultured; tkáňové podpůrné struktury; Osteogenesis; Polyglycolic Acid; kyselina polyglykolová; chondroitinsulfáty; Cell Engineering; buněčné inženýrství